An Analysis of the Reading Comprehension Levels of Class VIII Students in Descriptive Texts at SMP Negeri 7 Medan - Silaen, Jesica C. F.; Theresia, Thania; Rahmawati, Rahmawati; Mayasari, Mayasari (Randwick International of Education and Linguistics Science Journal, 2024)
This study aims to analyze the reading comprehension levels of Class VIII students in descriptive texts at SMP Negeri 7 Medan. Reading is a fundamental skill for language learners, especially for students learning English as a foreign language. However, many students face difficulties in comprehending descriptive texts, such as identifying key details, understanding the structure, and drawing accurate conclusions. These challenges are attributed to limited vocabulary, lack of familiarity with descriptive text conventions, and ineffective reading strategies. This research will evaluate students' comprehension levels and the effectiveness of current teaching strategies and materials. The findings are expected to provide insights that contribute to the improvement of reading instruction and strategies, benefiting both students and educators, and enhancing literacy education in junior high schools across Indonesia.